Keanekaragaman Spesies Pemangsa Thrips (Thysanoptera:Thrypidae) di Sekitar Pertanaman Cabai (Capsicum annuum L.) di Dataran Rendah dan di Lahan Lebak Wilayah Jambi - Asni Johari; Dewi Dewi Sartiami (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2013)
Predatory thrips species is very important to restrain pest population in the field. This study was conducted to explore and analyze the diversity of predatory thrips species in and around chili planting in the lowland and swamp areas in Jambi. The survey was conducted at 13 sites in the lowlands and 6 sites in the swamp areas. The survey found 22 species of thrips predators in lowlands and 6 six species in swamp areas which are grouped into nine families. Predatory thrips species in the lowlands were Ammoplanus sp., Cheilomenes sexmaculata, Chilocorus melanophthalmus, Chilocorus ruber, Chrysopoda sp., Coccinella repanda,